2008
DOI: 10.1080/14786430701848046
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of nickel in single- and polycrystalline Cr2O3

Abstract: Chromia protective layers are formed on many industrial alloys to prevent corrosion by oxidation. Their role is to limit the inward diffusion of oxygen and the outward diffusion of cations. A number of chromia-forming alloys contain nickel as a component, such as steels, FeNiCr and NiCr alloys. To ascertain if chromia is a barrier to outward diffusion, nickel diffusion in chromia was studied in both single crystals and polycrystals in the temperature range 900-1100 C at an oxygen pressure of 10 À4 atm (argon þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The second possible mechanism would involve the interface between the chromia nodules and the mixed chromite spinel due to cations diffusion via the chromium oxide nodules. From literature data [27] and [28] Ni SC D −24 cm 2 s −1 referring respectively to References [27] and [28], where α is the segregation factor) are significantly lower than the grain boundaries diffusion coefficient of oxygen in mixed chromite. However, when the density of Cr 2 O 3 nodules becomes significant, the cations diffusion via chromia nodules probably becomes the rate-controlling step of the growth of mixed chromite.…”
Section: O Sc Dmentioning
confidence: 94%
“…The second possible mechanism would involve the interface between the chromia nodules and the mixed chromite spinel due to cations diffusion via the chromium oxide nodules. From literature data [27] and [28] Ni SC D −24 cm 2 s −1 referring respectively to References [27] and [28], where α is the segregation factor) are significantly lower than the grain boundaries diffusion coefficient of oxygen in mixed chromite. However, when the density of Cr 2 O 3 nodules becomes significant, the cations diffusion via chromia nodules probably becomes the rate-controlling step of the growth of mixed chromite.…”
Section: O Sc Dmentioning
confidence: 94%
“…However, for the longer oxidation time (28 days) nickel and manganese are found to be enriched in the outer part of the scale. This can be explain by the diffusion rates of these two elements in Cr 2 O 3 : Lobnig et al [39] showed that at 900°C manganese has a lattice-diffusion coefficient in a chromia layer grown on a Fe-20Cr-12Ni about two orders of magnitude higher than chromium (D = 1 9 10 -14 cm 2 s -1 for Mn and D = 8 9 10 -16 cm 2 s -1 for Cr autodiffusion for a 4 h annealing time), and work from Sabioni et al [40] showed that diffusion rate of nickel is higher than autodiffusion of chromium in chromine at 900°C.…”
Section: Rate Of Diffusion Versus Thermodynamical Stabilitymentioning
confidence: 95%
“…Figure 5 (a) implies that the nickel ions in the anodes may diffuse into the interface between the cathode and electrolytes. The nickel seems to have penetrated through the grain boundary and the pores of the electrolyte to the cathode layer during the sintering in high temperature [23][24][25][26].…”
Section: Characterizations and Single Cell Testsmentioning
confidence: 99%